(untitled) (Jurnal Bahasa, 2015)
The phonetic value of the grapheme n and ny in Malay has been questioned since the 19th century. Some scholars say that the grapheme n in the circumstance -nc- and -nj- as in the words ancam and panjang carries the same phonetic value as the grapheme ny [ɲ] (modern IPA) as in the words nyawa and banyak. The recording data collected from 20 subjects, employing the computer-aided acoustical phonetic method, was analysed. It was found that the phonetic value of the grapheme n appearing in the circumstance -nc- and -nj- is different from that of the grapheme ny throughout all the data examined. This finding is supported by the articulatory phonetic method that all the subjects applied. However, a new question arose here. The phonetic value of the nasal hard-palate sound ny [ɲ], as traditionally identified, becomes doubtful because in all the subjects, the middle of the tongue did not touch the hard palate at the time of ny articulation. They, on the other hand, gave responses whereby the grapheme ny was articulated by the blade of tongue touching the postalveoli or by the front part of the tongue touching the alveolo-palate. Our computer-aided acoustical analysis proves that the grapheme ny produces two continuing sounds as [ĭn] when the recording data was decoded in the reverse. Based on this experiment, I propose the hypothesis that the phone of the grapheme ny followed by a vowel sound is produced by double articulation, i.e. palatalization [nj]. Palatalization does not occur for the grapheme n that appears in the circumstance -nc- and -nj- in Malay. Keywords: alveolar, post-alveolar, alveolo-palatal, palatal, palatalization, double articulation